Discovery and Elucidation of Counteranion Dependence in Photoredox Catalysis - Farney, Elliot P; Chapman, Steven J; Swords, Wesley B; Torelli, Marco D; Hamers, Robert J; Yoon, Tehshik P (Journal of the American Chemical Society, 2019)
Over the past decade, there has been a renewed interest in the use of transition metal polypyridyl complexes as photoredox catalysts for a variety of innovative synthetic applications. Many derivatives of these complexes are known, and the effect of ligand modifications on their efficacy as photoredox catalysts has been the subject of extensive, systematic investigation. However, the influence of the photocatalyst counteranion has received little attention, despite the fact that these complexes are generally cationic in nature. Herein, we demonstrate that counteranion effects exert a surprising, dramatic impact on the rate of a representative photocatalytic radical cation Diels–Alder reaction. A detailed analysis reveals that counteranion identity impacts multiple aspects of the reaction mechanism. Most notably, photocatalysts with more noncoordinating counteranions yield a more powerful triplet excited state oxidant and longer radical cation chain length. It is proposed that this counteranion effect arises from Coulombic ion-pairing interactions between the counteranion and both the cationic photoredox catalyst and the radical cation intermediate, respectively. The comparatively slower rate of reaction with coordinating counteranions can be rescued by using hydrogen-bonding anion binders that attenuate deleterious ion-pairing interactions. These results demonstrate the importance of counteranion identity as a variable in the design and optimization of photoredox transformations and suggest a novel strategy for the optimization of organic reactions using this class of transition metal photocatalysts.